A PP4 holoenzyme balances physiological and oncogenic nuclear factor-kappa B signaling in T lymphocytes - Brechmann, Markus; Wabnitz, Guido H.; Nicolay, Jan Peter; Booken, Nina; Samstag, Yvonne; Klemke, Claus-Detlev; Boutros, Michael (Immunity, 2012)
Summary: Signal transduction to nuclear factor-kappa B (NF-κB) involves multiple kinases and phosphorylated target proteins, but little is known about signal termination by dephosphorylation. By RNAi screening, we have identified protein phosphatase 4 regulatory subunit 1 (PP4R1) as a negative regulator of NF-κB activity in T lymphocytes. PP4R1 formed part of a distinct PP4 holoenzyme and bridged the inhibitor of NF-κB kinase (IKK) complex and the phosphatase PP4c, thereby directing PP4c activity to dephosphorylate and inactivate the IKK complex. PP4R1 expression was triggered upon activation and proliferation of primary human T lymphocytes and deficiency for PP4R1 caused sustained and increased IKK activity, T cell hyperactivation, and aberrant NF-κB signaling in NF-κB-addicted T cell lymphomas. Collectively, our results unravel PP4R1 as a previously unknown activation-associated negative regulator of IKK activity in lymphocytes whose downregulation promotes oncogenic NF-κB signaling in a subgroup of T cell lymphomas.
Published online: October 18, 2012
Gesehen am 25.06.2018